Cognitive deficits in bipolar disorder: from acute episode to remission - Volkert, J.; Schiele, M. A.; Kazmaier, Julia; Glaser, Friederike; Zierhut, K. C.; Kopf, J.; Kittel-Schneider, S.; Reif, A. (European archives of psychiatry and clinical neuroscience, 2016)
Considerable evidence demonstrates that neuropsychological deficits are prevalent in bipolar disorder during both acute episodes and euthymia. However, it is less clear whether these cognitive disturbances are state- or trait-related. We here present the first longitudinal study employing a within-subject pre- and post-testing examining acutely admitted bipolar patients (BP) in depression or mania and during euthymia, aiming to identify cognitive performance from acute illness to remission. Cognitive performance was measured during acute episodes and repeated after at least 3 months of remission. To do so, 55 BP (35 depressed, 20 hypo-/manic) and 55 healthy controls (HC) were tested with a neuropsychological test battery (attention, working memory, verbal memory, executive functioning). The results showed global impairments in acutely ill BP compared to HC: depressed patients showed a characteristic psychomotor slowing, while manic patients had severe deficits in executive functioning. Twenty-nine remitted BP could be measured in the follow-up (dropout rate 48 %), whose cognitive functions partially recovered, whereas working memory and verbal memory were still impaired. However, we found that subthreshold depressive symptoms and persisting sleep disturbances in euthymic BP were associated with reduced speed, deficits in attention and verbal memory, while working memory was correlated with psychotic symptoms (lifetime). This result indicates working memory as trait related for a subgroup of BP with psychotic symptoms. In contrast, attention and verbal memory are negatively influenced by state factors like residual symptoms, which should be more considered as possible confounders in the search of cognitive endophenotypes in remitted BP.